Prostate cancer: unmet clinical needs and RAD9 as a candidate biomarker for patient management - Lieberman, Howard B. (Transl Cancer Res, 2018)
Prostate cancer is a complex disease, with multiple subtypes and clinical presentations. Much progress has been made in recent years to understand the underlying genetic basis that drives prostate cancer. Such mechanistic information is useful for development of novel therapeutic targets, to identify biomarkers for early detection or to distinguish between aggressive and indolent disease, and to predict treatment outcome. Multiple tests have become available in recent years to address these clinical needs for prostate cancer. We describe several of these assays, summarizing test details, performance characteristics, and acknowledging their limitations. There is a pressing unmet need for novel biomarkers that can demonstrate improvement in these areas. We introduce one such candidate biomarker, RAD9, describe its functions in the DNA damage response, and detail why it can potentially fill this void. RAD9 has multiple roles in prostate carcinogenesis, making it potentially useful as a clinical tool for men with prostate cancer. RAD9 was originally identified as a radioresistance gene, and subsequent investigations revealed several key functions in the response of cells to DNA damage, including involvement in cell cycle checkpoint control, at least five DNA repair pathways, and apoptosis. Further studies indicated aberrant overexpression in approximately 45% of prostate tumors, with a strong correlation between RAD9 abundance and cancer stage. A causal relationship between RAD9 and prostate cancer was first demonstrated using a mouse model, where tumorigenicity of human prostate cancer cells after subcutaneous injection into nude mice was diminished when RNA interference was used to reduce the normally high levels of the protein. In addition to activity needed for the initial development of tumors, cell culture studies indicated roles for RAD9 in promoting prostate cancer progression by controlling cell migration and invasion through regulation of ITGB1 protein levels, and anoikis resistance by modulating AKT activation. Furthermore, RAD9 enhances the resistance of human prostate cancer cells to radiation in part by regulating ITGB1 protein abundance. RAD9 binds androgen receptor and inhibits androgen-induced androgen receptor's activity as a transcription factor. Moreover, RAD9 also acts as a gene-specific transcription factor, through binding p53 consensus sequences at target gene promoters, and this likely contributes to its oncogenic activity. Given these diverse and extensive activities, RAD9 plays important roles in the initiation and progression of prostate cancer and can potentially serve as a valuable biomarker useful in the management of patients with this disease.